Gardens of water : [compact disc, unabridged] : a novel - Drew, Alan, 1970- (Random House, 2008)
When an earthquake hits Pakistan Sinan Basioglu, a devout Muslim and his family must depend on their American neighbors for survival. Sinan doesn't like this because his daughter and the American teacher's son are having a secret relationship and she is trying to escape Kurdish tradition.